NUMERICAL STUDY OF THE INFLUENCE OF THE PRESSURE IN THE BURNER CHAMBER ON THE COMBUSTION OF THE LIQUID FUEL - S.A. Bolegenova (Вестник. Серия физическая, 2010)
The research of the influence of the pressure in the chamber on the combustion of the liquid spray fuel on the basis of the solution of differential equations of turbulent reacting flow has been performed. The distributions of fuel, water, oxygen and temperature in the burner chamber have been obtained.